Evolution of Yrast states and B(E2 : 8₁⁺ → 6₁⁺ ) VALUES OF ¹¹⁴, ¹¹⁶, ¹¹⁸, ¹²⁰, ¹²²Cd by interacting boson model (IBM-1) - Hossain, I.; Abdullah, Hewa Y.; Ahmed, I.M.; Murarak, A.A. (Вопросы атомной науки и техники, 2015)
In this paper we address the evolution of yrast levels of low-lying structure in the neutron-rich even-even ¹¹⁴⁻¹²²Cd nuclei within the framework of interaction boson model (IBM-1). The reduced transition probabilities B(E2) ↓ between 8₁⁺ to 6₁⁺ states of even-even neutron rich Cd nuclei for N = 66; 68; 70; 72; 74 have been calculated by IBM-1 and compared with the previous available experimental values. The calculated values of ¹¹⁴, ¹¹⁶, ¹¹⁸, ¹²⁰, and ¹²²Cd, are 0.272 e²b², 0.281 e²b², 0.259 e²b², 0.190 e²b² and 0.149 e²b² respectively. The ratio of the excitation energies of the first 4⁺ and the first 2⁺ excited states, R₄/₂, were also calculated for those nuclei. The ¹¹⁴⁻¹²²Cd isotopes in U(5) - O(6) transitional symmetry were investigated. We have studied the systematic B(E2) values as a function of even neutrons from N = 66 to 74. Furthermore as a measure to quantify the evolution, we have studied systematically the ground state energy ratios RL = E(L⁺) / E(21⁺ ) and transition rate R = B(E2 : L⁺ → (L - 2)⁺) / B(E2 : 2⁺ → 0⁺) of some of the low-lying quadrupole collective states in comparison to the available experimental data. Представлена еволюція yrast-рівнів низько-лежачої структури в богатому нейтронами парно-парному ядрі ¹¹⁴⁻¹²²Cd у рамках моделі взаємодіючих бозонів (IBM-1). Вірогідності змінених (reduced) переходів B(E2) ↓ між станами 8₁⁺ і 6₁⁺ в богатому нейтронами парно-парному ядрі Cd для N = 66; 68; 70; 72; 74 були розраховані за допомогою IBM-1 і порівняні з раніше відомими експериментальними величинами. Розраховані величини ¹¹⁴Cd, ¹¹⁶Cd, ¹¹⁸Cd, ¹²⁰Cd і ¹²²Cd і дорівнюють 0.272 e²b², 0.281 e²b², 0.259 e²b², 0.190 e²b² та 0.149 e²b², відповідно. Співвідношення енергій збудження першого 4⁺ та першого 2⁺ збуджених станів R₄/₂ були розраховані для цих ядер. ¹¹⁴⁻¹²²Cd ізотопи в U(5) - O(6) симетрії переходів були досліджені. Ми дослідили систематику B(E2) величин, як функцію парних нейтронів від N = 66 до 74. Крім того, вивчаючи кількісно еволюцію, ми систематично вивчили співвідношення енергій основних станів RL = E(L⁺) / E(21⁺ ) та величину R = B(E2 : L⁺ → (L - 2)⁺) / B(E2 : 2⁺ → 0⁺) для переходів кількох низько-розміщених квадрупольних колективних станів та порівняли з наявними експериментальними даними. Представлена эволюция yrast-уровней низколежащей структуры в богатом нейтронами четно-четном ядре ¹¹⁴⁻¹²²Cd в рамках модели взаимодействующих бозонов (IBM-1). Вероятности измененных (reduced) переходов B(E2) ↓ между состяниями 8₁⁺ и 6₁⁺ в богатом нейтронами четно-четном ядре Cd для N = 66; 68; 70; 72; 74 были расчитаны с помощью IBM-1 и сравнены с ранее известными экспериментальными величинами. Рассчитанные величины ¹¹⁴Cd, ¹¹⁶Cd, ¹¹⁸Cd, ¹²⁰Cd и ¹²²Cd равны 0.272 e²b², 0.281 e²b², 0.259 e²b², 0.190 e²b² и 0.149 e²b², соответственно. Отношения энергий возбуждения первого 4⁺ и первого 2⁺ возбужденных состояний R₄/₂ были рассчитаны для этих ядер. ¹¹⁴⁻¹²²Cd изотопы в U(5) - O(6) симметрии переходов были исследованы. Мы исследовали систематику B(E2) величин, как функцию четных нейтронов от N = 66 до 74. Кроме того, изучая количественно эволюцию, мы систематически изучили отношения энергий основных состояний RL = E(L⁺) / E(21⁺ ) и величину R = B(E2 : L⁺ → (L - 2)⁺) / B(E2 : 2⁺ → 0⁺) для переходов нескольких низколежащих квадрупольных коллективных состояний и сравнили с доступными экспериментальными данными.